M|G|∞ queue busy period length with PME distribution analysis through Laplace transform - Ferreira, M. A. M. (Acta Scientiae et Intellectus, 2018)
In this article it is shown that if the busy period of a M|G|∞ queue system is PME distributed, the respective service time is a random variable with a long-tail distribution. The result is obtained through Laplace transforms analysis.